The effect of the educational program using athletics competitions in school sports curricula on the development of some elements of physical fitness for in (8-10) years-old children - البوصافي ماجد بن سعيد; داود بن محمد بن سليمان البلوشي; بدرية بنت خلفان بن عيسى الهدابي (Journal of Sport Science Technology and Physical Activities, 2025)
The study aimed to identify the impact of the educational program using athletics competitions for children in school sports curricula on the development of some elements of physical fitness for pupils of the age group (8-10) years. The study sample consisted of (70) male and female students, divided equally by (35) male and female students from the third grade, and (35) male and female students from the fourth grade. The study showed the results: that the use of the athletics program for children in the school sports curricula was characterized by excitement and suspense, which positively affected the effectiveness of the class and the performance of the students